Asymmetric organocatalytic Michael addition of cyclopentane-1,2-dione to alkylidene oxindole - Silm, Estelle; Järving, Ivar; Kanger, Tõnis (Beilstein Journal of Organic Chemistry, 2022)
An asymmetric Michael reaction between cyclopentane-1,2-dione and alkylidene oxindole was studied in the presence of a multifunctional squaramide catalyst. Michael adducts were obtained in high enantioselectivities and in moderate diastereoselectivities.
Keywords: cyclopentane-1,2-dione; enantioselective catalysis; Michael addition; organocatalysis; squaramide

(untitled) - Sharma, D.; Kumar, M.; Das, P. (Synth. Commun., 2021)

(untitled) - Shokova, E. A.; Kim, J. K.; Kovalev, V. V. (Russ. J. Org. Chem., 2015)

(untitled) - de Gonzalo, G.; Alcántara, A. R. (Pharmaceuticals, 2021)

(untitled) - Rueping, M.; Kuenkel, A.; Tato, F.; Bats, J. W. (Angew. Chem., Int. Ed., 2009)

(untitled) - Rueping, M.; Volla, C. M. R.; Bolte, M.; Raabe, G. (Adv. Synth. Catal., 2011)

(untitled) - Nair, D. K.; Menna-Barreto, R. F. S.; da Silva Júnior, E. N.; Mobin, S. M.; Namboothiri, I. N. N. (Chem. Commun., 2014)

(untitled) - Ramireddy, N.; Abbaraju, S.; Ding, D.; Arman, H.; Zhao, J. C.-G. (J. Heterocycl. Chem., 2017)

(untitled) - El-Sepelgy, O.; Haseloff, S.; Alamsetti, S. K.; Schneider, C. (Angew. Chem., Int. Ed., 2014)

(untitled) - Xian, J.; Chen, L.; Ye, L.; Sun, Y.; Shi, Z.; Zhao, Z.; Li, X. (Tetrahedron, 2019)

(untitled) - Gao, Y.-Q.; Hou, Y.; Chen, J.; Zhen, Y.; Xu, D.; Zhang, H.; Wei, H.; Xie, W. (Org. Biomol. Chem., 2021)

(untitled) - Staunton, J.; Wilkinson, B. (Chem. Rev., 1997)

(untitled) - Mosnáček, J.; Weiss, R. G.; Lukáč, I. (Macromolecules, 2004)

(untitled) - Wolkenberg, S. E.; Wisnoski, D. D.; Leister, W. H.; Wang, Y.; Zhao, Z.; Lindsley, C. W. (Org. Lett., 2004)

(untitled) - Deng, X.; Mani, N. S. (Org. Lett., 2006)

(untitled) - Herrera, A. J.; Rondón, M.; Suárez, E. (J. Org. Chem., 2008)

(untitled) - Ding, D.; Zhao, C.-G. (Tetrahedron Lett., 2010)

(untitled) - Rueping, M.; Kuenkel, A.; Fröhlich, R. (Chem. – Eur. J., 2010)

(untitled) - Ren, Q.; Li, M.; Yuan, L. (Org. Biomol. Chem., 2017)

(untitled) - Paju, A.; Kanger, T.; Pehk, T.; Eek, M.; Lopp, M. (Tetrahedron, 2004)

(untitled) - Paju, A.; Kostomarova, D.; Matkevitš, K.; Laos, M.; Pehk, T.; Kanger, T.; Lopp, M. (Tetrahedron, 2015)

(untitled) - Jõgi, A.; Paju, A.; Pehk, T.; Kailas, T.; Müürisepp, A.-M.; Lopp, M. (Tetrahedron, 2009)

(untitled) - Preegel, G.; Noole, A.; Ilmarinen, K.; Järving, I.; Kanger, T.; Pehk, T.; Lopp, M. (Synthesis, 2014)

(untitled) - Preegel, G.; Ilmarinen, K.; Järving, I.; Kanger, T.; Pehk, T.; Lopp, M. (Synthesis, 2015)

(untitled) - Preegel, G.; Silm, E.; Kaabel, S.; Järving, I.; Rissanen, K.; Lopp, M. (Synthesis, 2017)

(untitled) - Silm, E.; Kaabel, S.; Järving, I.; Kanger, T. (Synthesis, 2019)

(untitled) - Fang, X.; Wang, C.-J. (Chem. Commun., 2015)

(untitled) - Okino, T.; Hoashi, Y.; Takemoto, Y. (J. Am. Chem. Soc., 2003)

(untitled) - Zhao, B.-L.; Li, J.-H.; Du, D.-M. (Chem. Rec., 2017)

(untitled) - Hamza, A.; Schubert, G.; Soós, T.; Pápai, I. (J. Am. Chem. Soc., 2006)

(untitled) - Izzo, J. A.; Myshchuk, Y.; Hirschi, J. S.; Vetticatt, M. J. (Org. Biomol. Chem., 2019)

(untitled) - Zhang, Z.; Schreiner, P. R. (Chem. Soc. Rev., 2009)

(untitled) - Brak, K.; Jacobsen, E. N. (Angew. Chem., Int. Ed., 2013)

(untitled) - Bartsch, H.; Eiden, F.; Buchborn, H. (Arch. Pharm. (Weinheim, Ger.), 1982)